Online test design for computer-based final examination preparation - Yuli Udiasih; Imam Ghozali (Universitas Sarjanawiyata Tamansiswa, 2019)
The objective of this research is to describe the way to design an online test for computer-based final examination preparation for Junior High School Students using Schoology application. The method used in this research is research and development. First, the researcher analyzed graduation competence standards for the 2017 and 2018 National Examinations, English basic competences in 2013 Curriculum, test indicators of 2017 and 2018 National Examinations, and 2017 and 2018 paper-based National Examinations. The result of the analysis was used to determine the skills, the basic competences, and the test indicators for the test blue print of the online test. Based on the test blue prints, the researcher developed the online test in Ms-Words. The developed test instrument was consulted with the researcher’s consultants to get the external validity. After the external validity was obtained, the test was uploaded in the Schoology application. The online test in the Schoology was put into a try out to students of Grade IX G and H of SMPN 1 Pengasih. The student’s scores in the test try out were analyzed using SPSS Product Moment. The result showed that the students’ scores in the test try out coincided with their scores in their end-semester test. This proved that the test is effective to be used. The test items which were not valid were revised through English teacher group discussion in SMPN 1 Pengasih. After being revised, the online test was ready to be used.